Subchronic Toxicity of Methanol Extract From Erythrina Variegata (Leguminosae) Leaves on Male Wistar Rats (Rattus Norvegicus) - Tati Herlina; Madihah Madihah; Deden Deni; Suseno Amien (Universitas Jenderal Soedirman, 2017)
Erythrina variegata is a herbal plant commonly used in Indonesia traditional medicine for treatment malaria disease. Acute toxicity test results showed that the methanol extract of E. variegata leaves categorized as practically nontoxic. In this study, we investigated sub chronic toxicity of the extract on male Wistar rats and the procedure based on guidelines of OECD 408 (1998) and EPA OPPTS 870.3100 (1998) for 90 constitutive days. The rats are classified into four dose groups were 0 (control), 250, 500, and 1000 mg/kg body weight with each group consist of five test animals. The results do not show toxic signs either behavior or body weight changed. Hematological analysis and clinical blood chemistry revealed slightly changes but were within the normal limits, except for BUN and SGPT values. Histopathological examination showed an increased damage of liver and kidney cells in form hydropic degeneration, fatty degeneration, as well as necrosis along with increased of extract doses that significantly different with control (p<0.05). However, the damage is reversible and was assumed had not has relations with the treatment. Thus, orally administration of E. variegata extract by dosage 250, 500, and 1000 mg/kg BW did not cause subchronic toxicity on male Wistar rats.